50 Influence of microRNA expression profiles on the efficacy of radiochemotherapy in locally advanced head and neck squamous cell carcinoma. Issue 5 (May 2015) - ,; Müer, A.; Weichert, W.; Stenzinger, A.; Budach, V.; Tinhofer, I.
Abstract : Introduction: Despite recent advances in radiochemotherapy, the treatment of locally advanced head and neck squamous cell carcinoma (HNSCC) is still challenging with 5-year survival rates less than 60% resulting from a high frequency of local and/or regional tumor recurrence. Hence, the investigation on molecular mechanisms that influence treatment efficacy and the identification of predictive molecular markers, which could improve patient selection for optimized treatment, are therefore of high clinical relevance. MicroRNAs (miRNA) as key regulators of gene expression and modulators of cancer progression are of rising interest as a source of such biomarkers. In this study we evaluated the impact of miRNA expression on the efficacy of radiochemotherapy on HNSCC. Methods: Formalin-fixed, paraffin-embedded archival tumor material was collected from patients with locally advanced HNSCC, who had been treated with hyperfractionated accelerated radiotherapy in combination with either 5-fluorouracil/cisplatin (5-FU/CDDP) or 5-fluorouracil/mitomycin C (5-FU/MMC) within the ARO0401 phase III trial. Using samples from a test cohort of 50 patients (tumor site only oropharynx) the microRNA profiles of tumor cells were established by Affymetrix miRNA microarrays. Results were validated in samples from 149 HNSCC patients (oropharynx and hypopharynx) by quantitative real-time PCR (qRT-PCR). Results: The expression levels of 15 miRNAs were identified to correlate with overall survival of patients treated with MMC-based chemoradiation, whereas the expression levels of 10 other microRNAs were correlated with overall survival of patients treated with CDDP-based chemoradiation. The expression pattern of miR-200b and miR-146a were validated by qRT-PCR, each of them being a significantly correlated miRNA in the respective study arm. Our results revealed that the correlation of the expression levels of these microRNAs was dependent on the tumor subsite, as a significant correlation was only observed in patients with oropharyngeal but not hypopharyngeal carcinomas. Interestingly, expression of miR-146a correlated with local recurrence, whereas miR-200b was associated with the occurrence of distant metastases. Conclusion: miRNA expression levels can be used as predictive markers for the efficacy of chemoradiation. The biological function of the candidate miRNAs identified in this study will be further investigated in HNSCC cell line models.